Bibliometrics and scientometrics analysis of exosomes relevance in hepatocellular carcinoma (2014-2024) - Wu, Kaikui; Lu, Guiya; Guo, Ruijun; Li, Chunxia; Ou, Minglin (Frontiers in Oncology, 2025)
BackgroundExosomes have emerged as pivotal players in the pathogenesis, progression, and treatment of hepatocellular carcinoma (HCC), establishing them as a major research focus in recent years. This bibliometric analysis maps the knowledge evolution and quantifies research trends in exosome-associated HCC studies from 2014 to 2024.MethodsWe retrieved relevant publications (2014-2024) from the Web of Science Core Collection (WoSCC) database and conducted bibliometric analyses using CiteSpace, VOSviewer, and R software.ResultsThe analysis encompassed 1,120 publications (714 research articles and 406 reviews), originating from 60 countries/regions and 4,035 institutions, published in 388 journals, and authored by 6,989 authors. China emerged as the most productive country, followed by the United States. The most prolific journals were the International Journal of Molecular Sciences and Frontiers in Oncology, while Fudan University ranked as the most productive institution. Trend analysis indicates that future HCC exosome research will concentrate on: the development and application of exosomes as HCC biomarkers, optimizing exosomes as drug delivery vehicles, investigating tumor treatment resistance, and exploring exosome-mediated immunotherapeutic strategies for HCC to facilitate their clinical application.ConclusionCurrent evidence demonstrates that the field of HCC exosome research is in a phase of rapid development, with its potential in both basic research and clinical translation continually being explored. Through bibliometric analysis, this study identifies key trends and emerging directions in HCC exosome research from 2014 to 2024, offering insights into current research priorities and potential innovations.